Determination of Socioeconomic and Demographic Factors Affecting Household Health Care Spending: The Case of Turkey - ÇEBİ KARAASLAN, Kübranur and AYSİN, Meryem and ÇALMAŞUR, Gürkan (International Journal of Contemporary Economics and Administrative Sciences, 2024)
Health care spending is a critical problem for any state that seeks to ensure that its citizens have equal access to essential health services. Are socioeconomic and demographic factors the determinants of health care spending? The motivation for the study is to find an answer to this question. The aim of the study is to evaluate the determinants of health care spending of households, which constitute one of the most essential unions that make up society within a socioeconomic and demographic framework. In this regard, the Tobit model was utilized in the study using official institution data. As a result of the study, it has been determined that socioeconomic and demographic factors have an impact on health care spending. It is expected that the results of the study will be beneficial to policy makers, decision makers and those who make researches about the factors that will ensure equality in health.